2019
DOI: 10.1002/chem.201904651
|View full text |Cite
|
Sign up to set email alerts
|

Red‐Emitting Delayed Fluorescence and Room Temperature Phosphorescence from Core‐Substituted Naphthalene Diimides

Abstract: Unprecedented ambient triplet‐mediated emission in core‐substituted naphthalene diimide (cNDI) derivatives is unveiled via delayed fluorescence and room temperature phosphorescence. Carbazole core‐substituted cNDIs, with a donor–acceptor design, showed deep‐red triplet emission in solution processable films with high quantum yield. This study, with detailed theoretical calculations and time‐resolved emission experiments, enables new design insights into the triplet harvesting of cNDIs; an important family of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…[3][4][5][6]59,64 Any compounds with closely-lying 1 CT, 3 CT and 3 LE states may exhibit TADF properties (or more generally, close-lying S 1 /T 1 states). 65,66 Recently, we prepared a compact, orthogonal electron donor-acceptor dyad, with naphthalimide (NI) as the electron acceptor and phenothiazine (PTZ) as the electron donor (Fig. 6).…”
Section: Observation Of Localized Triplet States: Different Isc Mecha...mentioning
confidence: 99%
“…[3][4][5][6]59,64 Any compounds with closely-lying 1 CT, 3 CT and 3 LE states may exhibit TADF properties (or more generally, close-lying S 1 /T 1 states). 65,66 Recently, we prepared a compact, orthogonal electron donor-acceptor dyad, with naphthalimide (NI) as the electron acceptor and phenothiazine (PTZ) as the electron donor (Fig. 6).…”
Section: Observation Of Localized Triplet States: Different Isc Mecha...mentioning
confidence: 99%
“…While arylene monoimides such as naphthalene monoimides and phthalimide derivatives are recently shown to exhibit ambient RTP, corresponding diimide derivatives are seldom exploited for triplet harvesting [8] . In this context, we have recently reported the ambient triplet harvesting of core‐substituted naphthalene diimides via RTP [4h] and thermally activated delayed fluorescence (TADF) [9] …”
Section: Figurementioning
confidence: 99%
“…(b) Phosphorescence properties may also be used for harvesting triplet excitons. Recent studies have shown that functionalized aromatic imides/amides can exhibit room-temperature phosphorescence by heavy atom substitution 61 or charge-transfer states, 62 and even exhibit transient and persistent mechanoluminescence at room temperature simultaneously which may be used to develop innovative applications in OLEDs. 61 (c) Combined with the AIE or AIDF effect, the PLQYs and EQEs of aromatic imide/amide-based emitters could be greatly improved to suppress the ACQ phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…(d) Lots of aromatic imide/amide optoelectronic materials are undeveloped as emitters in OLEDs, such as naphthalene diimide, 62 thieno [3,4-c]pyrrole-4,6-dione, 63,64 bithiophene imide (BTI), 65,66 and isoindigo. 67,68 BTI has the same heptagonal imide structure as BPI, thus serving as a promising building block of emitters.…”
Section: Discussionmentioning
confidence: 99%